PENGARUH GOOD CORPORATE GOVERNANCE DAN SUSTAINABILITY REPORTING TERHADAP NILAI PERUSAHAAN (TOBIN’Q) PADA EMITEN SEKTOR PROPERTY & REAL ESTATE YANG TERDAFTAR DI INDEKS SAHAM SYARIAH INDONESIA (ISSI) PERIODE 2021-2024 - Intan Putri Rahayu; Asriani Asriani; Weny Rosilawati (Universitas Dharmawangsa, 2026)
Company value is an important indicator that reflects investors' perception of the company's performance and prospects, especially in the property and real estate sectors that are experiencing development dynamics. This study aims to analyze the influence of Good Corporate Governance (GCG) and Sustainability Reporting on the value of the company (Tobin's Q) in property and real estate sector issuers listed on the Indonesian Sharia Stock Index (ISSI) for the 2021-2024 period. This study uses a quantitative approach with a causal associative method. The data used is secondary data in the form of annual reports, sustainability reports, and company financial statements published through the official website of the Financial Services Authority (OJK) and each company, using the Purposive Sampling technique. Data analysis was carried out using panel data regression with the Fixed Effect Model (FEM) model. The results of the study show that partially the Audit committee has a positive and significant effect on the company's value, while the board of directors, independent commissioners, and sustainability reporting do not have a significant effect on the company's value. This study concludes that other factors outside the model are more dominant in influencing the company's value. The implications of this study show that companies need to improve the effectiveness of governance and the quality of sustainability disclosures to increase investor confidence